The anticonvulsant effects of Ducrosia anethifolia (Boiss) essential oil are produced by its main component alpha-pinene in rats - Zamyad, Mahnaz; Abbasnejad, Mehdi; Esmaeili-Mahani, Saeed; Mostafavi, Ali; Sheibani, Vahid (Arquivos de Neuro-Psiquiatria, 2019)
Ducrosia anethifolia has been recommended as a remedy for neurological disorders. However, the anticonvulsant effects of D. anethifolia essential oil (DAEO) and its major constituent α-pinene have not yet been clarified.Methods: A rat model of pentylenetetrazole (PTZ)-induced convulsions was used. Oxidant and antioxidant parameters were assayed in the temporal lobe.Results: The data showed that DAEO (50, 100 and 200 mg/kg, i.p.) and α-pinene (0.2 and 0.4 mg/kg i.p.) delayed the initiation time, and reduced the duration of myoclonic and tonic-clonic seizures following PTZ injection. The PTZ produced oxidative stress so that malondialdehyde and hydrogen peroxide levels were increased and catalase and peroxidase activity decreased. Pretreatment with DAEO and α-pinene significantly inhibited the above-mentioned enzymatic changes in PTZ-treated animals.Conclusion: The results suggest that α-pinene, at teast in part, was responsible for the induction of the anticonvulsant and antioxidant effects of DAEO in rats.
Keywords: Pentytenetetrazote; seizures; oxidative stress